Exploring carbon quantum dots as an aqueous electrolyte for energy storage devices. (15th November 2022) - Kumar, Satendra; Goswami, Manoj; Singh, Netrapal; Sathish, N.; Reddy, M.V.; Kumar, Surender
Abstract: The facile accessibility of electroactive species to the surface of graphene-based supercapacitors is crucial. Here, we report the potential of carbon quantum dots (CQDs) as an electrolyte for graphene-based supercapacitors. The aqueous CQDs electrolyte properties are explored and compared with other commonly used aqueous electrolytes. A gravimetric capacitance of 155 F/g at a current density of 1 A/g is achieved with an aqueous 25 mM CQDs electrolyte having 0.43 S/cm ionic conductivity. The energy density of as-fabricated device is calculated to be ~55 Wh/kg at a power density of 3200 W/kg with a 1.6 V potential window (PW). Also, our approach comprises a solution-based flexible and free-standing CQDs-polymer gel (f-CPG) electrolyte film formation. The f-CPG film reveals an ionic conductivity of 0.48 S/cm and a high dielectric constant (972) with low dielectric loss (~12) at 2 MHz frequency at room temperature. The f-CPG electrolyte film exhibits a considerable electrochemical performance with gravimetric capacitance, energy, and power densities of 140 F/g, 50 Wh/kg, and 8534 W/kg at 2 A/g, respectively. The CQDs electrolyte could be an excellent choice for energy storage devices. Graphical abstract: The 25 mM aqueous CQD electrolyte shows a significant potential window of 1.6 V, high ionic conductivity of 0.43, and 0.48 S/cm (in f-CPG film) at room temperature. The fabricated device shows 155 F/g specific capacitance at 1 A/g current density with a 1.6 V potential window. A high energy and power density of 55 Wh/kg and 3200 W/kg is calculated with 72 % capacitance retention after 1000 life cycles at a current density of 6 F/g. The developed f-CPG separator film also shows 140 F/g specific capacitance at a current density of 2 A/g. Unlabelled Image Highlights: CQDs are synthesized by the pyrolysis method shows high ionic conductivity of 0.43 S/cm A 25 mM aqueous CQDs electrolyte shows a potential window of 1.6 V with a specific capacitance of 155 F/g at 1 A/g in full cell configuration. It shows a high energy density of 55 Wh/kg at a power density of 3200 W/kg. The prepared f-CQDs film shows a high dielectric constant (~972) and low dielectric loss (~12) at a 2 MHz frequency. The capacitance for f-GPG electrolyte film was found at 140 F/g at 2 A/g under a 1.6 V working potential window.